Cote d'Ivoire : 2021 Article IV Consultation-Press Release; Staff Report; Informational Annex; Debt Sustainability Analysis; Selected Issues; and Statement by the Executive Director for Cote d'Ivoire. (IMF Staff Country Reports; Country Report ;, 2021)
Cote d'Ivoire has shown strong resilience to the pandemic, owing to the authorities' swift policy reaction and to a decade of sound macroeconomic policies, as well as the support of the international community including the IMF.